Innovations in knowledge and learning postsecondary education reform to support employment and inclusive growth. - Sarvi, Jouko E. (Metro Manila, Philippines Asian Development Bank, 2017)
To meet modern day challenges of improving quality and relevance, responding to new knowledge, and strengthening teaching and learning, the postsecondary education space must revise system structures, content designs, and delivery strategies, i.e., engage in disruptive thinking. Governments need to implement effective regulatory processes to ensure quality and equitable access by all students. Education programs must be in sync with workplace needs and built around knowledge clusters rather than specialized fields. Diverse and multiple disruptions will become the norm.
Keywords: Teaching education -- Economic aspects; Vocational education -- Economic aspects; Education -- Higher education; Electronic books